Walk 12 HEALTH RESORT AND PARK - Lidin, Konstantin; Grigoryeva, Elena; Baryshnikov, Vitali; Karpov, Sergey; Bolshakov, Andrei (project baikal, 2014)
Walk 12 HEALTH RESORT AND PARK Development Plan for the Northern Part of the Sverdlovsky District in Irkutsk The Glazkovsky Necropolis in Irkutsk: an Archaeological Monument of Global Importance Sketch Design of Water and Health Complex on the Territory of the Park of the Paris Commune in Irkutsk Sketch of the Master Plan and Zoning of the Park of the Paris Commune in Irkutsk The Sports Axis of the Left Bank of Irkutsk. Reconstruction of the Sports Complex "Locomotive" Museum and Conservation Complex "Glazkovsky Necropolis"